Zinc inhibition of γ-aminobutyric acid transporter 4 (GAT4) reveals a link between excitatory and inhibitory neurotransmission - Cohen-Kfir, Einav (National Academy of Sciences, 2005)
γ-Aminobutyric acid (GABA) transporters (GATs) play an important role in inhibitory neurotransmission by clearing synaptically released GABA and by maintaining low resting levels of GABA in synaptic and extrasynaptic regions. In certain brain regions, vesicular zinc is colocalized and coreleased with glutamate and modulates the behavior of a number of channels, receptors, and transporters. We examined the effect of zinc on expressed GATs (GAT1, GAT2, GAT3, and GAT4) in Xenopus laevis oocytes by using tracer flux and electrophysiological methods. We show that zinc is a potent inhibitor of GAT4 (K(i) of 3 μM). Immunolocalization of GAT4 in the hippocampus revealed dense localization in the CA1 and CA3 regions of the hippocampus, regions which are known to be heavily populated by zinc-containing glutamatergic neurons. The results suggest a physiological role of synaptically released zinc in the hippocampus, because zinc released from hyperactive glutamatergic neurons may simultaneously bring about elevated GABAergic inhibition. Therefore, this mode of zinc function signifies a link between excitatory and inhibitory neurotransmission and may play a neuroprotective role against glutamate-induced excitotoxicity.